The psychological impact of students choosing the department at SMKN 2 Yogyakarta. (June 2020) - Putrianti, L; Astuti, B
Abstract: This study aims to find out how the psychological impact of students who are forced by parents in choosing majors at SMKN 2 YOGYAKARTA. Factors causing major discrepancies taken due to the compulsion of parents. Parents should discuss in terms of children's interests and talents, so that children can freely develop their talents and interests. this study uses a descriptive qualitative approach, with a type of case study research. The subject of this study was the tenth-grade students at SMKN 2 Yogyakarta. Data collection techniques using the method of observation, interviews, and documentation. Test the validity of using a test of credibility by passing. Data analysis techniques that will be performed in this study using Creswell The school, especially the teacher, seeks to give attention and motivation to students so that students can perform well.